Determinants of customer satisfaction with the online shopping environment: evidence from India. (24th October 2022) - Gupta, Sahil; Aggarwal, Arun; Mittal, Amit; Chand, Pawan Kumar
Due to its practical importance, the relationship between customer satisfaction and the shopping environment has attracted many researchers. Various studies have established a close relationship between these two concepts and have tested them time and again. This relationship has shown to impact the traditional ways of shopping and has implications for the emerging field of online shopping in the context of an emerging market such as India. To address this, the current study aims to cover the various aspects of shopping which lead to customer satisfaction. Responses were collected from 543 online shoppers to understand their expectations and experience in the online shopping environment during the Indian festive season where Indians tend to shop a lot. A gap analysis was done to understand the difference between the experience and expectations of the shoppers and its impact was calculated using regression for predicting customers' satisfaction. The results show that 'product return policy', 'delivery' and 'warranty' have a strong impact while 'quality of interaction' and 'mode of payment' strategies may require emphasising different aspects of a customer's shopping experience than retention strategies.